The Influence of Integration of Four Skills to the Performance of Undergraduate Students on TOEFL Sample Test - Nurul Azizah Ria Kusrini; Eka Rizki Amalia (LP3M STITNU AL HIKMAH MOJOKERTO, 2021)
Nowadays, there are a number of approaches to teach English. All of them have been used and developed along the time to help the foreign students to reach a better proficiency of English as foreign language. For few years, there have been many opinions that reinforce the idea of integrating four skills to create a real communication atmosphere as authentic as possible. They propose to mix reading and listening comprehension with oral and written expression in teaching English. Hence, this investigation aims to identify whether by including integration of four skills into the lesson can bring significant affects or not to the performance of undergraduate students in doing a TOEFL sample test. To reach this, observation of lessons will be recorded on checklist and the application of a standardized test will be applied in order to establish the relationship between two variables, the integration of four skills in lesson and the affects to the students’ performance in doing TOEFL sample test. Finally, it can be properly affirmed that the integration of the four skills of the English language influences the students’ performance concerning English as a foreign language.